2017
DOI: 10.1038/srep45360
|View full text |Cite
|
Sign up to set email alerts
|

Laser beam melting 3D printing of Ti6Al4V based porous structured dental implants: fabrication, biocompatibility analysis and photoelastic study

Abstract: Fabricating Ti alloy based dental implants with defined porous scaffold structure is a promising strategy for improving the osteoinduction of implants. In this study, we use Laser Beam Melting (LBM) 3D printing technique to fabricate porous Ti6Al4V dental implant prototypes with three controlled pore sizes (200, 350 and 500 μm). The mechanical stress distribution in the surrounding bone tissue is characterized by photoelastography and associated finite element simulation. For in-vitro studies, experiments on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 30 publications
1
51
0
2
Order By: Relevance
“…Another pro is that 3D printers with production process in the powder bed allow for reusing the utilized powder and reduction in waste quantities that would arise during conventional fabrication methods such as Computerized Numerical Control (CNC) cutting. Numerous literature reports show successfully printed dental [ 6 , 7 , 8 , 9 ], craniofacial [ 10 , 11 , 12 ] and orthopedic implants [ 13 , 14 , 15 ] using selective laser melting (SLM) and electron beam melting (EBM) technologies. The SLM stands out because in enables fabrication of very fine structures with complex internal architectures and overhangs with precision and shape fidelity higher than the EBM [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another pro is that 3D printers with production process in the powder bed allow for reusing the utilized powder and reduction in waste quantities that would arise during conventional fabrication methods such as Computerized Numerical Control (CNC) cutting. Numerous literature reports show successfully printed dental [ 6 , 7 , 8 , 9 ], craniofacial [ 10 , 11 , 12 ] and orthopedic implants [ 13 , 14 , 15 ] using selective laser melting (SLM) and electron beam melting (EBM) technologies. The SLM stands out because in enables fabrication of very fine structures with complex internal architectures and overhangs with precision and shape fidelity higher than the EBM [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The premise was that the method should be tunable, offering the possibility of attaching different moieties according to specific needs, and should also be stable in order to resist the harsh conditions of the in vivo environment, particularly in the oral cavity. We opted for Ti 6 Al 4 V ELI alloy because it is widely used in the dental implant industry [36], and chose 3D-printed Ti 6 Al 4 V ELI pieces because metal 3D printing techniques are opening the field of implantology to increasingly improved designs in order to tackle the biomechanical issue [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the cultured osteosarcoma cell line MG-63 exhibited more successful proliferation and osteoconduction with only 30% porosity in comparison to the 50% porosity scaffold groups. Yang et al investigated the optimal pore size (200, 350, or 500 µm) of bone tissue implants and found that the 350 µm scaffolds exhibited a better expression level of osteogenic genes [34]. In addition, the optimal pore size for ligament tissue ingrowth in braided ligament scaffolds in PLAGA 10:90 braids was found to be between 175 and 233 µm [35].…”
Section: Properties Of Ia3dmentioning
confidence: 99%